Impact of part time work on the academic performance of international students / Ershad Ali - Ali, Ershad (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
The study analyses the impact of part time work on academic performance of international students while they study. In doing so, the study has conducted a survey among international students who were studying at different tertiary institutes in Auckland region. The study found that there are positive as well as negative impacts on the students’ academic performance while they study as well as work. The study opines that whether the impact would be positive or negative depends on time management between work and study. Findings of the study may be of interest for policy makers, educationists, and researchers.